Effectiveness of Risk Management through Risk Maturity Measurement: A Study at PT Pelabuhan Indonesia - Utami, Lestari; Pasaribu, Rina Djunita (Jurnal Manajemen Pelayanan Publik, 2024)
This research aims to evaluate the effectiveness of risk management at Pelindo post-merger and assess its risk management maturity level. Additionally, the study intends to offer relevant recommendations for the company in developing its risk management strategy and implementation. The research adopts a qualitative descriptive approach with a case study strategy, where the researcher analyzes an organization as a unit of analysis in a natural setting without manipulation. Data collection techniques include interviews with representatives from the Group Risk Management, Governance, and Compliance as the corporate-level risk managers. Document analysis includes textbooks, academic and professional journals, theses, articles, and company department reports. Data analysis follows the Miles and Huberman model. The research indicates that the maturity level of risk management at Pelindo post-merger has reached the good practice phase with a score of 2.94. This reflects a consistent application of risk management in accordance with industry standards, although its effectiveness varies. The organizational structure, framework, processes, and risk culture have begun to be implemented. Recommendations for improvement include strengthening the risk culture, enhancing the effectiveness of risk management functions, and aligning risk strategies with the ERM transformation plan for better effectiveness and compliance.